Neural Conduction Along Postretinal Visual Pathways in Glaucoma - Parisi, Vincenzo; Ziccardi, Lucia; Tanga, Lucia; Roberti, Gloria; Barbano, Lucilla; Carnevale, Carmela; Manni, Gianluca; Oddone, Francesco (Frontiers in Aging Neuroscience, 2021)
Purpose: To evaluate the retinal ganglion cells (RCG) function and the neural conduction along the post-retinal large and small axons and its correlation with retinal nerve fiber layer thickness (RNFL-T) in open angle glaucoma (OAG) eyes. Methods: Thirty-seven OAG patients (mean age: 51.68±9.83 years) with 24-2 Humphrey mean deviation (MD) between -2.5 and - 20 dB and IOP < 21 mmHg in pharmacological treatment (OAG Group) and 20 age-matched controls (Control Group) were enrolled. In both Groups, simultaneous pattern electroretinograms (PERG) and visual evoked potentials (VEP), in response to checks stimulating macular or extramacular areas (the check edge subtended 15’ and 60’of visual arc, respectively), and RNFL-T (measured in superior, inferior, nasal and temporal quadrants) were assessed. Results: In OAG Group, a significant (ANOVA, p<0.01) reduction of 60’ and 15’ PERG P50-N95 and VEP N75-P100 amplitudes and of RNFL-T [Overall (average of all quadrants) or Temporal] with respect to Controls was found; the values of 60’ and 15’ PERG P50 and VEP P100 implicit times and of Retinocortical Time (RCT; difference between VEP P100 and PERG P50 implicit times) were significantly (p<0.01) increased with respect to control ones. The observed increased RCTs were significantly linearly correlated (Pearson’s Test, p<0.01) with the reduced PERG amplitude and MD values, whereas no significant linear correlation (p<0.01) with RNFL-T (Overall or Temporal) values was detected. Conclusions: In OAG there is an impaired post-retinal neural conduction along both large and small axons (increased 60’ and 15’ RCT) that is related to RGC dysfunction, but independent from the RNFL morphology. This implies that, in OAG, the impairment of post-retinal neural structures can be electrophysiologically identified and may contribute to the visual field defects, as suggested by the linear correlation between the increase of RCT and the MD reduction.